Study of operating modes of electromagnetic hammer with adjustable impact energy and blow frequency - Al-Rawashdeh, Ayman Y.; Pavlov, Vlademer E. (Institute of Advanced Engineering and Science, 2024)
The current work was designed to study the operating modes of electromagnetic impact mechanism (electromagnetic hammer) comprising idle and working stroke windings that are enclosed in magnetic conductor, and reciprocating ferromagnetic striker. Investigation was conducted by modelling in MATLAB environment and performing verification tests with different hammers. Simulation model of the hammer was derived using experimentally obtained static characteristic curves of flux linkage and thrust force for each of the windings. Results revealed that at maximum working stroke winding voltage-varying idle stroke winding voltage, the impact energy did not change, but the impact frequency varied between 0-187 bpm. At maximum idle stroke winding voltage and working stroke winding voltage ranging between 0 to maximum value, the impact energy varied between 84-360 J, the impact frequency varied between 96-187 bpm. Maximum losses over the working cycle were associated with electric losses in the hammer windings and can be reduced by reducing winding currents through increasing the striker speed. The mathematical model of the current study allowed quantifying energy parameters of the electromagnetic hammer. The impact machine cycle includes three operating modes, each determines the main energy parameters: efficiency, impact energy, and cycle time.